Antarctic krill peptide alleviates liver fibrosis via downregulating the secondary bile acid mediated NLRP3 signaling pathway. Issue 14 (28th June 2022) - Yue, Hao; Li, Yanqi; Cai, Weizhen; Bai, Xiaolin; Dong, Ping; Wang, Jingfeng
Abstract : The Antarctic krill peptide supplement remodeled the gut microbiota and downregulated secondary bile acid-mediated NLRP3 signaling to improve liver fibrosis. Abstract : Liver fibrosis is a necessary process for liver disease. Recent studies have reported that the enterohepatic circulation of bile acid plays a vital role in developing liver fibrosis. The Antarctic krill peptide (AKP) has been proved to have a variety of activities such as antioxidant and anti-inflammatory, but any possible influence on liver fibrosis remains unclear. In the current study, the liver fibrosis mice were intraperitoneal injection of carbon tetrachloride (2.5%, 10 mL kg −1 ) and oral administration AKP (400 mg kg −1 ) for 30 days. The results showed that the AKP supplement decreased the serum ALT and AST levels, reduced the content of liver TNF-α and Collagen I, and improved liver inflammation and fibrosis, which was also confirmed by H&E and Masson staining. Bile acid is an important metabolite for the gut microbiota. We found that the AKP supplement alleviated the gut microbiota dysbiosis remarkably, as indicated by increased species richness and diversity, and decreased overgrowth of genera Bifidobacterium, Lactobacillus, Bacteroides, Clostridiales and Fusicatenibacter. Furthermore, AKP mediated gut microbiota improvement decreased the intestinal bile salt hydrolase and 7α-dehydroxylation activities, resulting in the decrease of secondary bile acid taurodeoxycholic acid (TDCA) and taurolithocholic acid (TLCA) concentrations. Mechanistically, AKP inhibited NLRP3 signal by downregulating the secondary bile acid, decreased cleaved Caspase-1 expression to suppress IL-1β-mediated hepatic stellate cell activation. This study reports for the first time that AKP improved liver fibrosis via improving the gut microbiota mediated bile acid-NLRP3 signaling, which might provide new ideas and evidence for Antarctic krill's high-value utilization.